Bladder granulocytic sarcoma in a child: case report and literature review - Tuna, Rumeysa; Çelik, Ayça İribaş and Kılıç, Suar Çakı and Bayramoğlu, Zuhal and Tuğcu, Deniz and Ünüvar, Ayşegül and Doğan, Öner and Anak, Sema and Oktar, Tayfun and Karaman, Serap and Karakaş, Zeynep (The Turkish Journal of Pediatrics, 2022)
Background. Granulocytic sarcoma (GS) is an extramedullary solid tumor composed of immature myeloid cells. GS has been associated with acute myeloid leukemia (AML), myelodysplastic syndromes or myeloproliferative diseases. Although GS can affect various tissues of the human body, it has rarely been reported in other soft tissues such as the breast, gastrointestinal, respiratory and genitourinary tracts. We report a pediatric case diagnosed with granulocytic sarcoma of the bladder and concomitant AML. Case. A twelve-year-old previously healthy girl was admitted to the pediatric urology clinic with a ten-day history of hematuria and pollakiuria. Laboratory examinations revealed anemia, thrombocytopenia and neutrophilic leukocytosis. Bone marrow aspiration results were consistent with acute myeloid leukemia -FAB subtype M2-. Abdominal magnetic resonance imaging (MRI) showed an irregularly bounded 12 cm mass on the right side of the bladder. Transurethral resection (TUR) pathology was consistent with granulocytic sarcoma. After a multimodal treatment approach, complete remission was achieved. Conclusions. Malignant bladder masses are rare causes of macroscopic hematuria in childhood. The diagnostic spectrum is wide, ranging from rhabdomyosarcoma to leukemia involvement. The bladder is a rare site of extramedullary involvement in pediatric patients with AML. Multimodal treatment should be considered on a per-patient basis.